Morphological and Elemental Evaluation of Investigative Mouthwashes to Repair Acid-Eroded Tooth Surface - Amaechi BT; Mohseni S; Dillow AM; Cvelich MH; Stevanovic A; Abah AI; Movaghari Pour F; Farah R; Kataoka Y; Restrepo MC; Zhang D; Leigh LE; et al. (Dove Medical Press, 2023)
Bennett Tochukwu Amaechi,1 Sahar Mohseni,1 Andrew M Dillow,1 Mackenzie H Cvelich,2 Ana Stevanovic,3 Alphonsus Igoche Abah,1 Fatemeh Movaghari Pour,1 Rayane Farah,1 Yuko Kataoka,1 Maria Camila Restrepo,1 Dennis Zhang,4 Leonora Ethleen Leigh,4 Joel Basilan4 1Department of Comprehensive Dentistry, University of Texas Health San Antonio, San Antonio, TX, USA; 2Department of Developmental Dentistry, University of Texas Health San Antonio, San Antonio, TX, USA; 3Kleberg Advanced Microscopy Center, University of Texas at San Antonio, San Antonio, TX, USA; 4Research & Development – Oral Care, BASF Corporation, Tarrytown, NY, USACorrespondence: Bennett Tochukwu Amaechi, Department of Comprehensive Dentistry, School of Dentistry, University of Texas Health San Antonio, 7703 Floyd Curl Drive, San Antonio, TX, 78229-3900, USA, Tel +1 210 567 3185, Email amaechi@uthscsa.eduPurpose: Erosive tooth wear (ETW) is characterized by subsurface demineralization and tooth substance loss with crater formation. Remineralization of subsurface demineralization has previously been demonstrated; however, repair of the eroded surface is still under investigation. This study investigated the effectiveness of mouthwashes containing hydrolyzed wheat protein (HWP) in repairing ETW through promotion of organized crystal growth.Methods: Enamel Erosion was created on 210 enamel blocks by 10-minute demineralization in 1% Citric Acid (pH 3.5). Then, blocks were randomly assigned to seven groups (30/group); (A) 0.2% HWP, B) 1% HWP, (C) 2% HWP, (D) 1% HWP + 0.05% NaF, (E) Listerine™ mouthwash, (F) 0.02% NaF Crest™ Pro-health mouthwash and (G) artificial saliva (AS) only. Groups were subjected to daily pH-cycling consisting of one 5-minute erosive challenge with citric acid, three 1-minute mouthwash treatment periods, and then storage in AS for the rest of the time for 28 days. Treatment effects were assessed using SEM-EDX. Statistical analysis was by ANOVA and Tukey’s multiple comparison.Results: In groups exposed to HWP-containing mouthwashes, there was growth of fiber-like crystals that increased in packing density in a dose-dependent manner (0.2%, 1%, 2%) on the eroded enamel surfaces, with increased calcium and phosphate contents on the treated surfaces. The non-HWP-containing groups had the eroded surfaces covered by structureless deposit layer firmly attached to the surface.Conclusion: Treating eroded enamel surface with HWP-containing mouthwash resulted in repair of the damaged tissue by formation of a protective layer of crystal deposits within and on the eroded enamel tissue.Keywords: hydrolyzed wheat protein, Enameguard, erosive tooth wear, acid erosion, erosion repair, remineralization